Mechanical Treatment of ZrB2–SiC Powders and Sintered Ceramic Composites Properties; Research and Development - 2016 - Buyakova S. P. Svetlana Petrovna; Knyazeva A. G. Anna Georgievna; Burlachenko A. G. Aleksandr Gennadjevich; Mirovoy Yu. A. Yury Aleksandrovich; Kulkov S. N. Sergey Nikolaevich (2018, 2018)
Title screen